Monocyte signature as a predictor of chronic lung disease in the preterm infant - Windhorst, Anita C.; Heydarian, Motaharehsadat; Schwarz, Maren; Oak, Prajakta; Förster, Kai; Frankenberger, Marion; Gonzalez Rodriguez, Erika; Zhang, Xin; Ehrhardt, Harald; Hübener, Christoph; Flemmer, Andreas W.; Hossain, Hamid; et al. (Frontiers in Immunology, 2023)
Inflammation is a key driver of morbidity in the vulnerable preterm infant exposed to pre- and postnatal hazards and significantly contributes to chronic lung disease, i.e. bronchopulmonary dysplasia (BPD). However, the early changes in innate immunity associated with BPD development are incompletely understood. In the present study, we demonstrated the early postnatal predominance of nonclassical (CD14+CD16++) and intermediate (CD14++CD16+) monocytes as well as a distinct, corresponding cytokine signature highlighting TNFα as a critical regulator in cord blood of infants developing BPD. Transcriptome analysis of immune networks revealed a monocyte-centered, profibrotic signature at birth with disease severity-dependent expression patterns. These findings could influence future diagnostic and treatment strategies targeting the monocytic cell and its progeny.